Multinomial Logistic Regression of Contraceptive’s Determinants and Unmet Need for Family Planning among Currently Married Women in India - Ayub Khan; Hari Shankar (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Background: India is the first nation of the world to formulate the national family welfare programme in 1952 with the objective of reducing the birth rate for population stabilization. More than 100 million women in less developed countries or about 17% of all married women would prefer to avoid pregnancy but are not using any form of family planning. Despite the government's many efforts, the unmet need for family planning in India is still 12.8%. The present study is aimed to assess prevalence of the unmet need for family planning, its determinants, and to analyze the relationship between use contraceptive method and unmet need for family planning among Currently Married Women in India. Materials and Methods: The present study uses139,278 currently married women from urban residence selected from the fourth round of national family health survey conducted during 2015-2016 in the country. Descriptive and multivariate analysis have been used to study the prevalence of unmet need for family planning and to examine the relationship between contraceptive method with its determinants among currently married women in India. Results: Study shows that total unmet need for family planning are 12% (i.e. 5% for spacing and 7% for limiting) among currently married women. Women of aged 15-19 are 21% unmet need for contraception in which 19% and 2% unmet need for spacing and for limiting respectively. Women with primary and higher educated are 13% and 32% more likely to choose modern and traditional method respectively over non-use compared to women having no education. Conclusion: Improved access to family planning services, better education, improved standard of living, and higher exposure to mass media can significantly decrease the unmet need of family planning.